Exchange transfusion for neonatal hyperbilirubinemia: an 8-year single center experience at a tertiary neonatal intensive care unit in Turkey. (22nd September 2014) - Hakan, Nilay; Zenciroglu, Aysegul; Aydin, Mustafa; Okumus, Nurullah; Dursun, Arzu; Dilli, Dilek
Abstract: Objective : The aim of present study was to evaluate the indications and the complications associated with neonatal exchange transfusion (ET) performed for hyperbilirubinemia. Methods : This study included overall 306 neonates who underwent ET between 2005 and 2012. The demographic characteristics of patients, causes of jaundice and adverse events occurred during or within 1 week after ET were recorded from their medical files. Those newborns that underwent ET were classified as either "otherwise healthy" or "sick" group. Results : Of the 306 patients who underwent ET, 244 were otherwise healthy and had no medical problems other than jaundice. The remaining 62 patients were classified as sick that had medical problems other than jaundice ranging from mild to severe. The mean gestational age was 37.6 ± 2.5 weeks and the mean peak total bilirubin levels was 25.8 ± 6.6 mg/dl. The mean age at presentation was 5.4 ± 3.8 d for all infants. The most common cause of hyperbilirubinemia was ABO isoimmunization (27.8%). None of newborns died secondary to ET. Three infants had had necrotizing enterocolitis, and also three infants had had acute renal failure. The most common encountered complications of ET procedure were hyperglycemia (56.5%), hypocalcaemia (22.5%) and thrombocytopenia (16%). Conclusions : Our data showed that ABO isoimmunization was the most common cause of hyperbilirubinemia. Even mortality was not seen, very rare but major gastrointestinal and renal complications were associated with ET. The majority of adverse events associated with ET were laboratory abnormalities mainly hyperglycemia, hypocalcaemia and thrombocytopenia which were asymptomatic and treatable.